Autocrine TNF is critical for the survival of human dendritic cells by regulating BAK, BCL-2, and FLIPL - Lehner, Manfred; Kellert, Beate; Dießenbacher, Philip; Leverkus, Martin (The journal of immunology, 2012)
The life span of dendritic cells (DCs) is determined by the balance of pro- and antiapoptotic proteins. In this study, we report that serum-free cultured human monocyte-derived DCs after TLR stimulation with polyinosinic acid-polycytidylic acid or LPS underwent apoptosis, which was correlated with low TNF production. Apoptosis was prevented by the addition of exogenous TNF or by concomitant stimulation with R-848, which strongly amplified endogenous TNF production. Neutralization of TNF confirmed that DC survival was mediated by autocrine TNF induced either by stimulation with R-848 or by ligation of CD40. DCs stimulated by polyinosinic acid-polycytidylic acid or IFN-β, another known inducer of DC apoptosis, were characterized by high levels and activation of the proapoptotic protein BAK. The ratio of antiapoptotic BCL-2 to BAK correlated best with the survival of activated DCs. Addition of TNF increased this ratio but had little effect on BAX and XIAP. Knockdown experiments using small interfering RNAs confirmed that the survival of activated and also of immature DCs was regulated by BAK and showed that TNF was protective only in the presence of FLIPL. Together, our data demonstrate that the survival of DCs during differentiation and activation depends on autocrine TNF and that the inhibition of BAK plays an important role in this process.
Im Titel ist das "L" bei FLIPL tiefgestellt
Gesehen am 11.07.2018